2021
DOI: 10.1002/nop2.971
|View full text |Cite
|
Sign up to set email alerts
|

Parents' experiences on the combined use of continuous subcutaneous insulin infusion and real‐time continuous glucose monitoring to manage Type 1 diabetes in their children: A systematic review and meta‐synthesis of qualitative studies

Abstract: The incidence of Type 1 diabetes (T1DM) has increased significantly in many countries worldwide (Manuwald et al., 2017). Although there was a lower incidence of T1DM in Chinese children, the incidence amongst children under 15 has been rising dramatically over the past two decades (Weng et al., 2018). It is estimated that there are over 4,000 new cases of T1DM in children annually in China (Weng et al., 2018). Without appropriate insulin treatment and optimal glycaemic control, the condition of children with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…23 A preliminary search of CINAHL, Embase, JBI Evidence Synthesis, and the Cochrane Database of Systematic Reviews was conducted in December 2022 and found 2 reviews. Luo et al 24 conducted a systematic review synthesizing the experiences and perspectives of parents on the combined use of CSII and real-time CGM to manage T1D in their children. Alvarenga et al 25 carried out a systematic mapping review of the use of CSII in children and adolescents with T1D.…”
Section: Introductionmentioning
confidence: 99%
“…23 A preliminary search of CINAHL, Embase, JBI Evidence Synthesis, and the Cochrane Database of Systematic Reviews was conducted in December 2022 and found 2 reviews. Luo et al 24 conducted a systematic review synthesizing the experiences and perspectives of parents on the combined use of CSII and real-time CGM to manage T1D in their children. Alvarenga et al 25 carried out a systematic mapping review of the use of CSII in children and adolescents with T1D.…”
Section: Introductionmentioning
confidence: 99%